2017
DOI: 10.1108/ecam-01-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Bid or no-bid decision factors of indigenous contractors in Nigeria

Abstract: Purpose The decision to bid or not to bid for new projects determines contractors’ propensity for business success or failure. The purpose of this paper is to investigate the factors that affect the decision of indigenous construction contractors to bid or not to bid in Nigeria. Design/methodology/approach Analysis was conducted on data from questionnaires received from 64 engineering management employees of leading construction companies which are members of Nigeria’s Federation of Construction Industry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 30 publications
5
53
1
Order By: Relevance
“…Added to this already complex situation is the fact that these factors have a high degree of complicated interrelations [8]. In addition, considering these factors in a limited time period presents another constraint [9]. This makes the process of considering all these factors practically impossible for the decision maker [10].…”
Section: Introductionmentioning
confidence: 99%
“…Added to this already complex situation is the fact that these factors have a high degree of complicated interrelations [8]. In addition, considering these factors in a limited time period presents another constraint [9]. This makes the process of considering all these factors practically impossible for the decision maker [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that bidding decisions are negatively influenced by risk perception; while, it is positively influenced by risk propensity. Olatunji et al [16] investigated the factors affecting the indigenous construction contractor's decision on the bidding decisions. A total of 64 engineering management employees are included from Nigerian construction industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Typically, the procedure of bidding involves two vital decisions which is bid price determination and decision to bid. [9] The majority of the models developed are with unfeasible expectations and the complexity of their mathematical processes makes it interesting for the user to understand his reasoning. Thought of many factors and contributions, need for wide interference from the user which limit the correctness of the decision.…”
Section: Introductionmentioning
confidence: 99%